The Impact of Pricing, and Product Quality on Purchasing Decisions: Role Digital Marketing as a Moderating - Herispon Herispon; Putri Sudriana (International Journal of Islamic Business and Management Review, 2023)
This study attempts to ascertain how factors related to product quality, competitive pricing, and digital marketing affect sales volume and how digital marketing modifies the relationship between sales volume and purchasing decisions at PT Sang Hyang Seri Marketing Branch Riau. In this study, information was gathered from 130 respondents via questionnaires, and SEM was used for analysis. Found that Digital marketing did not show any support when employed as a moderating variable between purchase decisions and sales volume, while all other variables studied had a substantial beneficial effect on purchasing decisions and sales volume, both concurrently and separately